Improving Students’ English Vocabulary Using “Guessing Meaning From Context” Strategy - Kurniawan, Iwan (English Education: Jurnal Tadris Bahasa Inggris, 2019)
The study aims to improve the students’ vocabulary at MTs Muhammad Daud of Pesawaran, Lampung, using Guessing Meaning from Context strategy. The study employs a classroom action research (CAR) method conducted in three cycles, coupled with a pretest and a posttest. The finding indicates that there is an increase in the students’ vocabulary after the treatment